Theoretical Study on Structure and Electronic Properties of 4H-Cyclopenta[2,1-b,3;4-b’]dithiopene S-oxide and Its CCl2 and CF2 Bridged Derivatives - Banjo Semire; Olusegun Ayobami Odunola (Indonesian Journal of Chemistry, 2015)
Quantum chemical calculations using semi-empirical, ab initio, density functional theory (DFT) and Møller plesset (MP2) methods were performed on 4H-Cyclopenta[2,1-b,3;4-b’]dithiopene S-oxide derivatives (i.e. bridged dithiophene S-oxides, BTOs). The geometries, stabilities, electronic and thermodynamic properties of the compounds were studied. The thermodynamic parameters calculated at PM3 were in good agreement with those calculated at B3LYP/6-31G(d) level. The band gap energies calculated at B3LYP/6-31G(d) level for the BTOs were lower than the un-substituted trithiophene but higher than 4H-Cyclopenta[2,1-b,3;4-b’]dithiopene. The absorption λmax calculated using TD-DFT was shifted to longer wavelength by successive replacement of methylene hydrogens of BTO by chlorine and fluorine atoms.